Nitric oxide reduces oxidative damage induced by water stress in sunflower plants - Cechin, Inês [UNESP]; Cardoso, Guilherme Sementili [UNESP]; Fumis, Terezinha de Fátima [UNESP]; Corniani, Natália [UNESP] (Instituto Agronômico de Campinas, 2015)
Drought is one of the main environmental constraints that can reduce plant yield. Nitric oxide (NO) is a signal molecule involved in plant responses to several environmental stresses. The objective of this study was to investigate the cytoprotective effect of a single foliar application of 0, 1, 10 or 100 µM of the NO donor sodium nitroprusside (SNP) in sunflower plants under water stress. Water stressed plants treated with 1μM SNP showed an increase in the relative water content compared with 0 μM SNP. Drought reduced the shoot dry weight but SNP applications did not result in alleviation of drought effects. Neither drought nor water stress plus SNP applications altered the content of photosynthetic pigments. Stomatal conductance was reduced by drought and this reduction was accompanied by a significant reduction in intercellular CO2 concentration and photosynthesis. Treatment with SNP did not reverse the effect of drought on the gas exchange characteristics. Drought increased the level of malondialdehyde (MDA) and proline and reduced pirogalol peroxidase (PG-POD) activity, but did not affect the activity of superoxide dismutase (SOD). When the water stressed plants were treated with 10 μM SNP, the activity of PG-POD and the content of proline were increased and the level of MDA was decreased. The results show that the adverse effects of water stress on sunflower plants are dependent on the external NO concentration. The action of NO may be explained by its ability to increase the levels of antioxidant compounds and the activity of ROS-scavenging enzymes.
Keywords: Photosynthesis; Reactive oxygen species; Antioxidant enzymes; Proline; Malondialdehyde